Language Functions Analysis in Seventh Grade Student English Textbook - Zildjian Afa; Mansyur Srisudarso; Putri Kamalia Hakim (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2022)
This paper is an attempt to analyze the use of language functions of the conversation text found in When English Rings a Bell textbook. To achieve this purpose, the conversation texts in the textbook are carefully analyze through Halliday’s (1975) language function model. The results reveal that the conversation texts in the textbook is lacking some of the language functions. In regard with this, some implications were proposed.